Rozwój IT jako czynnik zmian w gospodarce - Cypryjański, Jacek (IT development as a change factor in economy, 2006)
One of the fundamental questions about IT concerns its impact on the economy. Rapid IT development makes this question constantly current and a reply to the question is of great significance for IT strategy development. The goal of the paper is to analyze main factors of IT development and its impact on the economy. The IT impact on the economy is discussed with the use of the Turban Model of Pressures and Responds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 167-174